The role of grandparents in the transition to parenting: a scoping review - Sousa, Ines (2023)
Introduction The transition to parenthood involves a set of intra and interpersonal changes, which affect not only the woman and her partner, but also the entire family system. Grandparents are highlighted as prominent figures in the contemporary family, constituting the main source of support for the family in this process. Therefore, it is extremely important to understand how grandparents can influence or not the transition to positive parenting, acting as facilitating agents or as hinderances in this process. Objective To map the available scientific evidence regarding the role of grandparents in the transition to parenthood of their children, encompassing the period of pregnancy, childbirth and the postpartum period up to 3 years. Methods This scoping review was developed according to the methodology of the Joanna Briggs Institute (JBI), 2020, with research carried out in April and May 2022 and updated in July 2023. Qualitative, quantitative or mixed studies were included, as well as review articles, published in English and produced between 2015 and 2023. This scoping review includes articles that address the role of grandparents in the context of the transition to parenting of their children, including the time of pregnancy, childbirth and the postpartum period up to 3 years. Results 11 articles that met the inclusion criteria were included. Four categories emerged: grandparents as a source of support; grandparents and their influence on family nutrition and exclusive breastfeeding; the ambivalence of feelings and the role of health professionals. Conclusion Grandparents can stand out as prominent elements of the family during the transition to parenting of their children, developing instrumental, emotional, informational and financial support roles; may influence exclusive breastfeeding and family nutrition. When concepts and beliefs about fundamental aspects relating to children differ, ambivalent feelings can arise and that lead to intergenerational conflicts. There is a gap in health care regarding the inclusion of meaningful people in the care of the couple and the child, in this case the grandparents.